Perbedaan Pengaruh Latihan Peregangan Sas-Balistik Dengan Pnf-Balistik Terhadap Fleksi Bilitas Trunkus Lansia - Kayun Sari; Sukadarwanto Sukadarwanto; S.Th Susilowati (Jurnal Keterapian Fisik, 2016)
Abstract : Elderly, SAS, Trunks, PNF. Elderly will be experienced by everyone who was blessed with longevity. Change is an advanced stage of development of life with a decrease in the body's ability to adapt to environmental stress. Decreased ability can be inhibited with the exercises. There are three stretches used is SAS, ballistic and PNF. This study is an experimental research design with two group pre test - post test design. The study was conducted at the Hospice Dharma Bhakti Surakarta in June-July 2007. The gauge trunk flexibility is Sit and Reach Test. 18 subjects showed flexibility can improve significantly after being treated SAS or PNF exercises,